Effects of Tai Chi combined with tDCS on cognitive function in patients with MCI: a randomized controlled trial - Xu, Ying; Zhu, Jingfang; Liu, Hong; Qiu, Zhijie; Wu, Mengyuan; Liu, Jiao; Wu, Jingsong; Huang, Jia; Liu, Zhizhen; Liu, Weilin; Tao, Jing (Frontiers in Public Health, 2023)
Background: Mild cognitive impairment (MCI) is a critical stage in dementia.Previous reviews have suggested that physical exercise combined with non-invasive brain stimulation is more beneficial in improving the cognitive function. However, no targeted studies have confirmed the effect of Tai Chi combined with transcranial direct current stimulation (tDCS) on the improvement of cognitive function in patients with MCI. Thus, this randomized trial was conducted to assess the effect of Tai Chi combined with tDCS on the cognitive performance of patients with MCI.Methods: From April 2018 to February 2020, a randomized, single-blind clinical trial was conducted, involving 180 participants with MCI who were divided into four intervention groups: Tai Chi combined with tDCS (TCT), Tai Chi combined with sham tDCS (TCS), walking combined with tDCS (WAT), and walking combined with sham tDCS (WAS). All participants were assessed at baseline and 12 weeks for global cognitive function, memory, attention, and executive function.Results: At baseline, there were no significant differences in age, gender, education duration, body mass index, or Baker Depression Inventory among the four groups (P ≥ 0.05). After 12 weeks of intervention, the TCT group showed greater improvements in MOCA scores, memory quotient scores, and digit-symbol coding task reaction time compared to the TCS, WAS, and WAT groups (P < 0.05). The TCT group also had a shorter Stroop test-color reaction time compared to the WAS and WAT groups (P < 0.05), a higher increase in Auditory Verbal Learning Test-immediate recall than the TCS and WAT groups (P < 0.05), a shorter visual reaction time than the TCS group (P < 0.05), and shorter sustained attention time compared to the WAT group(P < 0.05).: Tai Chi combined with tDCS effectively improves the global cognitive performance, memory, execution function and attention in patients with MCI. These findings suggest the potential clinical use of Tai Chi combined with tDCS as a physical exercise combined with non-invasive brain stimulation intervention to improve the cognitive function in older adults with MCI. Trial registration number: ChiCTR1800015629 (Chinese Clinical Trial Register).